Spillover potential of social media as catalyst to political action in the case of the Save palawan Movement - Baleva, Alisa Guiam (2012)
"Social media is slowly becoming a part of Philippine history by providing a venue to voice out concerns and opinions about various issues. Since the Internet offers opportunities for civic and political involvement which empowers people to participate, it is important to realize the extent of its potential for it to be fully maximized. Thus, this study determined how the utilization of online social media for collective action results to offline manifestation in the case of the No to Mining in Palawan campaign. Through content and textual analysis, survey, focus interview, and observation, data on the various aspects of the campaign were obtained from the public, participants, government and the Save Palawan Movement. Results showed that participants were well-versed about the campaign and the Movement which enabled them to take part in online discourse. Overall, participants primarily utilized the Movement's social media accounts for expression or publicizing one's stance on the issue. Through the participants' collective usage of the Movement's online social media accounts in support of the campaign, their voice on the issue is amplified. This, together with the collected signatures for the campaign can pressure government officials to produce policies which coincide with the Movement's stance."